The effect of d-pinitol on 50 kilometer time trial performance - Rust, Jay (My University, 2001)
Previous studies have demonstrated the effectiveness of glucose supplementation during prolonged exercise. The purpose of this study was to determine whether d-pinitol, a purported augmenter of glucose transport would have any practical effect on glucose uptake, and cycle time trial performance.
Keywords: Dietary supplements - Physiological effect; Cycling - Physiological aspects; Inositol - Physiological effect